THE EFFECT OF USING CIRCLE GAME ON STUDETS’ VOCABULARY MASTERY AT THE FOURTH GRADE OF MI DARUL ULUM KATEMAS KEMBANGBAHU LAMONGAN - Kholidah zahrotun Nisa'; Riryn Fatmawaty (Universitas Islam Lamongan, 2018)
Vocabulary is one of the component of language. Therefore, vocabulary is one of lanuage elements considerednnecessary for language. Game as a media in teaching vocabulary to students’ elementary school. The use of game would stimulate them to be more active and game was really matched with the students’. The researcher assumed that the use of game is good and effective ways to teach and to motivate them as young learners to study. The purpose of this study is to measure the effect of using circle game as the method in teaching vocabulary mastery. The research was conduct in March-May 2017. The subject of the study was all students at the fourth grade of MI Darul Ulum Katemas. Which is consists of 14 students. The method used in this research is pre-experimental research. The researcher uses sample one class. The research instrument is test. The test consists of pre-test and post-test. The result of the test is analyzed using paired t-test. The result showed that t value is -10.201 and df (degree of freedom) is 13. The researcher used the degree of significance 0.01/2 = 0.005. In the table of significance, it can be seen on the df 13 and on the degree of significance 0.005 (t-table 3.105). If t-value is compared to the t-table of the degree of significance, the result is t = -10.201 < 3.105. It means that there is significance improvement of the students’ vocbulary mastery through circle game. However, in the reserch, the researcher used two tailed test that compares the value of pre-test and post-test. It said as two tailed test, because t-table is divided in two (negative and positive) and put it on the right and left. After analyzing the result of t-test, the researcher used the degree of significance of 0.01/2 = 0.005, t-table = 3.105, and the researcher conclude that Ho is rejected and Ha is accepted, because the result of tvalue = -10.201 located in the area rejected of Ho, thus Ho is rejected and Ha is accepted. Based on the result of the study, the researcher concludes that circle game is effective method used in improving students’ vocabulary mastery and makes the students more interest and fun in learning English. Key words: Circle game, vocabulary mastery.